When the art of perfect timing - Albert, Stuart, 1941- (Jossey-Bass, 2013)
"An elegant and counterintuitive guide to achieving perfect timing Timing is everything. Whether we are making strategic business decisions or the smallest personal choice, we must decide not only what to do, but when to do it. Act too early--or too late--and the results can be disastrous. Based on a 20-year investigation into more than 2,000 timing issues and errors, When presents a single and practical approach for dealing with timing in life and business. Good timing, Albert argues, is not just a matter of luck, intuition, or past experience--all of which may be unreliable--but a skill. He describes that skill and details the tools and methods needed to conduct a successful timing analysis. The book is the first to offer an efficient and comprehensive way to think through any timing issue Filled with dozens of lively stories illustrating good and bad timing in all walks of life--business, warfare, medicine, sports, entertainment and the arts Written by Stuart Albert, one of the foremost timing experts in the world and developer of the first practical, research-based method for turning the skill of timing into a competitive advantage Engaging and counterintuitive, When will show everyone, regardless of the work they do, or the life they live, that 'it's all in the timing.'"--